2020
DOI: 10.1016/j.physbeh.2020.113030
|View full text |Cite
|
Sign up to set email alerts
|

Variations of estimated maximal aerobic speed in children soccer players and its associations with the accumulated training load: Comparisons between non, low and high responders

Abstract: The aim of this study was twofold: (i) to examine the variations of estimated maximal aerobic speed between non, low and high responders and (ii) to analyze the relationships between accumulated training load parameters and variations of maximal aerobic speed in children soccer players. Forty-four male soccer players were assessed three times during the early and mid-season (second to fifth month of the season) and were monitored daily over the period of analysis using the rating of perceived exertion (RPE), r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 45 publications
1
17
0
Order By: Relevance
“…Moreover, VO 2max between EaS to MiS was significantly related to PHV. Following the present study, Clemente et al (2020a) also reported significant improvements in maximal aerobic speed over the season in young soccer players, with the greatest improvements at the EnS (4 months after baseline test). However, Dragijsky et al (2017) showed an improvement in endurance, with the highest levels reported in the EaS, followed by a partial fall in the MiS, as well as at the EnS.…”
Section: Discussionsupporting
confidence: 74%
See 3 more Smart Citations
“…Moreover, VO 2max between EaS to MiS was significantly related to PHV. Following the present study, Clemente et al (2020a) also reported significant improvements in maximal aerobic speed over the season in young soccer players, with the greatest improvements at the EnS (4 months after baseline test). However, Dragijsky et al (2017) showed an improvement in endurance, with the highest levels reported in the EaS, followed by a partial fall in the MiS, as well as at the EnS.…”
Section: Discussionsupporting
confidence: 74%
“…However, Dragijsky et al (2017) showed an improvement in endurance, with the highest levels reported in the EaS, followed by a partial fall in the MiS, as well as at the EnS. Findings from this study can most likely be explained by the possible changes in anthropometric traits, heart and lung mass, and nervous system maturation associated with normal growth and maturation leading to improvement in aerobic capacity (Malina et al, 2015;Clemente et al, 2020a).…”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations
“…It satisfies the criterion for the sample size in SEM of being at least five times the number of the measurable item [69]. In addition, according to Clemente et al [70] and Maccallum and Bryant [71], the minimum sample size was estimated using Gpower software (University of Dusseldorf, Dusseldorf, Germany). The size of the sample was calculated to ensure α of 0.05 and power at 1-β = 0.80, and the result indicated a sample of 279, which is less than we have included (N = 615).…”
Section: Data Collection and Samplingmentioning
confidence: 99%